Flotation separation of copper–molybdenum sulfides using chitosan as a selective depressant. (November 2015) - Li, Mingyang; Wei, Dezhou; Liu, Qi; Liu, Wenbao; Zheng, Jimin; Sun, Hongjie
Highlights: Chitosan was used as a selective depressant in copper–molybdenum sulfides flotation​. The results showed the selective adsorption of chitosan on chalcopyrite. The depression mechanism of chitosan was studied by adsorption, FTIR spectra and ToF-SIMS. Abstract: Chitosan, a natural biodegradable polymer, was studied as a selective depressant in copper–molybdenum sulfide separation by flotation. Although chitosan depressed both molybdenite and chalcopyrite in single mineral flotation, selective flotation was achieved during the flotation of molybdenum-bearing copper sulfide concentrate at pH 6; the recovery of molybdenum in the froth product was over 70% while the recovery of copper was less than 24%. Adsorption measurements showed that chitosan had a higher adsorption density on chalcopyrite than on molybdenite. FTIR and ToF-SIMS measurements were carried out to confirm the different degrees of interaction of chitosan with molybdenite and chalcopyrite and the results showed that chitosan mostly adsorbed on chalcopyrite via amide groups when both molybdenite and chalcopyrite were present in the suspension.